2017
DOI: 10.2147/ndt.s114786
|View full text |Cite
|
Sign up to set email alerts
|

Contemplating stem cell therapy for epilepsy-induced neuropsychiatric symptoms

Abstract: Epilepsy is a debilitating disease that impacts millions of people worldwide. While unprovoked seizures characterize its cardinal symptom, an important aspect of epilepsy that remains to be addressed is the neuropsychiatric component. It has been documented for millennia in paintings and literature that those with epilepsy can suffer from bouts of aggression, depression, and other psychiatric ailments. Current treatments for epilepsy include the use of antiepileptic drugs and surgical resection. Antiepileptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 132 publications
(206 reference statements)
0
13
0
Order By: Relevance
“…Currently, more and more experimental and clinical research demonstrated the bidirectional relation between epilepsy and associated comorbidities [61][62][63]. Patients with epilepsy, especially with disabling epilepsy, clinically demonstrate not only recurrent seizures, cognition deficits and psychiatric symptoms such as depression and psychosis.…”
Section: Overexpression Of Adk and Comorbidities Associated Epilepsymentioning
confidence: 99%
“…Currently, more and more experimental and clinical research demonstrated the bidirectional relation between epilepsy and associated comorbidities [61][62][63]. Patients with epilepsy, especially with disabling epilepsy, clinically demonstrate not only recurrent seizures, cognition deficits and psychiatric symptoms such as depression and psychosis.…”
Section: Overexpression Of Adk and Comorbidities Associated Epilepsymentioning
confidence: 99%
“…Firstly, it is likely that this process can be initiated due to the loss of either hippocampal GABAergic interneurons (Sloviter, 1987), which would prompt axon outgrowth aimed to establish connections with new target cells, or septal parvalbumin-containing cells (also GABAergic) (Sanabria et al, 2006), which would disinhibit local circuits within the MS/DB. Should this be the case, implementation of recently developed novel treatment strategies based on stem cell therapy, in particular transplantation of GABAergic precursor cells (Lippert et al, 2018;Rao et al, 2017;Yasuhara et al, 2013), may lead to restoration of the septohippocampal projection system, thereby removing excessive cholinergic drive upon dentate molecular layer. Another possibility is that fiber sprouting can be triggered by neuroinflammatory signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell-based therapeutic approaches have been reported in different neurological diseases including stroke, multiple sclerosis, and Parkinson's disease, but have also been explored as a potential treatment for epilepsy (Rao et al 2017). Many studies focused on repairing and enhancing the GABAergic system by transplantation of GABAergic progenitor cells into epileptic brain regions .…”
Section: Cell Therapiesmentioning
confidence: 99%